Editorial for the Special Issue: “Radio Occultations for Numerical Weather Prediction, Ionosphere, and Space Weather” - Michael Gorbunov (Remote Sensing, 2023)
Sounding of the Earth’s ionosphere is an important application of the RO technique [...]